Regional impacts of warming on biodiversity and biomass in high latitude stream ecosystems across the Northern Hemisphere - Michelle C. Jackson; Nikolai Friberg; Luis Moliner Cachazo; David R. Clark; Petra Thea Mutinova; Eoin J. O’Gorman; Rebecca L. Kordas; Bruno Gallo; Doris E. Pichler; Yulia Bespalaya; Olga V. Aksenova; Alexander Milner; et al. (Communications Biology, 2024)
Abstract Warming can have profound impacts on ecological communities. However, explorations of how differences in biogeography and productivity might reshape the effect of warming have been limited to theoretical or proxy-based approaches: for instance, studies of latitudinal temperature gradients are often conflated with other drivers (e.g., species richness). Here, we overcome these limitations by using local geothermal temperature gradients across multiple high-latitude stream ecosystems. Each suite of streams (6-11 warmed by 1-15°C above ambient) is set within one of five regions (37 streams total); because the heating comes from the bedrock and is not confounded by changes in chemistry, we can isolate the effect of temperature. We found a negative overall relationship between diatom and invertebrate species richness and temperature, but the strength of the relationship varied regionally, declining more strongly in regions with low terrestrial productivity. Total invertebrate biomass increased with temperature in all regions. The latter pattern combined with the former suggests that the increased biomass of tolerant species might compensate for the loss of sensitive species. Our results show that the impact of warming can be dependent on regional conditions, demonstrating that local variation should be included in future climate projections rather than simply assuming universal relationships.